Margaret Cavendish and Causality - Duran, Jane (Philosophy & theology, 2017)
Lines of argument taken from Cavendish’s Observations and Letters are used to support the notion that her innovative metaphysics was designed to counter the thinking of the new science and Descartes’s own arguments. The work of Broad, Atherton and Lichtenstein is cited, and it is concluded that Cavendish deserves close reading. In addition, although Cavendish does not address notions having to do with Christianity as directly as we might wish, it is clear that these concepts are crucially related to her work.